A randomised, double masked, clinical trial of high dose vitamin A and vitamin E supplementation after photorefractive keratectomy. Issue 5 (1st May 2001) - Vetrugno, Michele; Maino, Anna; Cardia, Giuseppina; Quaranta, Grazia Maria; Cardia, Luigi
Abstract : AIM: To evaluate the effect of a high dose vitamin A and E supplementation on corneal re-epithelialisation time, visual acuity and haze following photorefractive keratectomy (PRK). METHODS: Two groups of 20 patients who underwent myopic PRK were supplemented with either 25 000 IU retinol palmitate and 230 mg α tocopheryl nicotinate or a placebo. Clinical outcomes were evaluated up to 360 days. RESULTS: In the vitamin treated group, re-epithelialisation time was significantly faster (p=0.029) and haze incidence was reduced (p=0.035), especially for high myopic corrections (p=0.043). This group also reported a significantly better uncorrected visual acuity (p=0.043). CONCLUSIONS: High dose vitamin A and E oral supplementation may accelerate re-epithelialisation time and may reduce corneal haze formation after PRK.